Landslide and Mudflow Behavior Case Study in Indonesia: Rheology Approach - Widjaja, Budijanto (IPTEK Journal of Proceedings Series, 2019)
Landslides and mudflows, both of which are triggered by rainwater and earthquakes, frequently occur in Indonesia. However, a conceptual and analytical understanding of these phenomena has yet to be achieved. The conventional calculation method (i.e., the limit equilibrium method) has not been able to predict the affected area after a landslide. Therefore, a rheological approach, the Bingham model (yield stress and viscosity), was applied in this research. Twelve cases of soil movement were assessed. High-plasticity silt is a type of fine soil with the potential to cause landslides and mudflows. This study comprises field data collection, soil sampling, laboratory testing, numerical modeling with a specific software, and result analyses. This study contributes explanation for the movement mechanism based on soil type, source area position to deposition area. New test laboratory innovation (flow box test) was introduced, and landslide and mudflow classification based on rheology approach were proposed. Examples of soil movement mitigation strategies are also presented to provide an overview of protective efforts against landslides and mudflows.